Life cycle cost to energy performance in green office buildings: a review of the component / Nurul Afiqah Yunus, Natasha Khalil and Kharizam Ismail - Yunus, Nurul Afiqah; Khalil, Natasha; Ismail, Kharizam (2021)
In today's critical economy, expectations have gone beyond the design and construction of a green building. The major barrier for growth in the green building market is the perception of higher first costs associated with these buildings. It has long been acknowledged that it is unacceptable to appraise the costs of projects only based on their initial costs. Hence, Life-Cycle Cost (LCC) is beneficial in allowing owners and clients to make an informed decision on the building materials. Through LCC, the total ownership of cost that includes operation and maintenance costs for a building item calculated in the design stage to get a more accurate projection. Ideally, the criteria or components of LCC should be determined before deciding to proceed with the project. However, the LCC components for green projects are fragmented and the items are not kept in a proper system. This situation can be challenging for the decision-makers to adopt LCC exercise as there is no proper guidance on the LCC components for green projects. Hence, this paper aims to review LCC components to energy elements in green office buildings from literature and desktop studies. The findings showed that the LCC components in the green building have similarities with conventional buildings such as acquisition cost, installation, operation and maintenance cost. However, green buildings acquire additional components such as energy consumption cost, building energy audit cost, and emission factors (non-monetary). The findings will serve as a basis of the LCC framework towards energy elements in green building.